1993
DOI: 10.1093/oxfordjournals.humrep.a138177
|View full text |Cite
|
Sign up to set email alerts
|

Unexplained infertility

Abstract: Unexplained infertility diagnosis is made in the presence of a normal semen analysis when tubal patency and normal ovulatory function are established. Among several potential causes, unexplained infertility could be attributed to vaginal pH and cervical mucus abnormalities. Although the vaginal canal and the cervix generally function as effective barriers to sperm, and although the production of mucus is essential to transport them from the vagina to the uterine cavity, these factors receive little attention i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(27 citation statements)
references
References 0 publications
0
27
0
Order By: Relevance
“…The European Society of Human Reproduction and Endocrinology (ESHRE) workshop concluded that ovarian stimulation with CC doubled the pregnancy rate in women with unexplained infertility [65]. An analysis by the Practice Committee of the American Society of Reproductive Medicine in 1998 of the effectiveness of different empiric regimens for unexplained infertility reported in 45 studies found the clinical pregnancy rate per cycle to be 5.6 % for CC alone and 8.3 % for CC-IUI compared to 1.3-3.4 % for no treatment [3].…”
Section: Treatment Resultsmentioning
confidence: 99%
“…The European Society of Human Reproduction and Endocrinology (ESHRE) workshop concluded that ovarian stimulation with CC doubled the pregnancy rate in women with unexplained infertility [65]. An analysis by the Practice Committee of the American Society of Reproductive Medicine in 1998 of the effectiveness of different empiric regimens for unexplained infertility reported in 45 studies found the clinical pregnancy rate per cycle to be 5.6 % for CC alone and 8.3 % for CC-IUI compared to 1.3-3.4 % for no treatment [3].…”
Section: Treatment Resultsmentioning
confidence: 99%
“…There may be two possibilities: (1) there is a real similarity in implantation in both treatment groups, or (2) there is a difference in implantations in both treatment groups, again not shown because of the lack of reaching the numbers needed.…”
Section: Discussionmentioning
confidence: 99%
“…A dose of hMG (150 IU) was given IM each day but could be individually adjusted to the ovarian response until at least 3 follicles 1 16 mm were achieved with approximately 1,000 pmol/l plasma E 2 for each follicle. Provided there was no excessive ovarian stimulation (plasma E 2 concentration 1 14,000 pmol/l), hCG (10,000 IU) was given IM and egg recovery by ultrasound (Combison 310, Kertztechnik, AG, Austria) guided needle aspiration transvaginally planned [1] 34-36 h afterwards. The retrieved eggs were handed to the embryologists to inseminate with prepared husband's semen and their development and cleavage monitored.…”
Section: Protocol Of Sivfmentioning
confidence: 99%
See 1 more Smart Citation
“…It is estimated that the incidence of infertility is 17% in the world and in 10% of these couples, the cause is not known [1,2] . There have been many postulates to explain…”
Section: Introductionmentioning
confidence: 99%